Social capital and social networks in the Malaysian corporate elite world: a conceptual framework - Chan, Kim Ling @ Geraldine (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
This article offers a conceptual understanding of the nature of social capital and social networks andtheir role in corporate elite organisation during capitalist big business growth in Malaysia, be it duringor after the 1990s rapid growth. It appreciates both notions as closely intertwined and hence, act asconceptual and analytical tools for explaining and understanding, particularly the nature of businessgroup organisation, in the 1990s or after. To date, although acknowledging the presence of networks,some analysts hardly focuses, conceptually and empirically, on corporate elite organisation based onsocial networks and social capital, particularly their structure and characteristics. Instead, they tend toexplain and analyse effects of the networks and also view them in the form of interpersonal dyadicties. This also implies that the nature of economic action, especially the organisation of businessgroups, appears to be carried out in a relatively atomised manner independent of social capital orsocial networks. Thus, the action is not fully understood. Based on some empirical findings mainlyfrom a sociological study conducted by the author on interlocking directorships and social networksof some multi-ethnic Malaysian corporate elite members of the 1990s, a conceptual framework isdeveloped. This article presents that framework which integrates the concept of social capital withthe concepts of social networks, human capital and interlocking directorships to allow an alternative ifnot better understanding of corporate elite and business group organistion in Malaysia, during or afterthe 1990s.